2021
DOI: 10.3390/ani11123514
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotics on Growth, Survival, Water Quality and Disease Resistance of Red Hybrid Tilapia (Oreochromis spp.) Fingerlings in a Biofloc System

Abstract: Biofloc technology has shown positive effects in aquaculture, especially on the growth performance of cultured animals. The aims of this study were to evaluate the effects of adding different probiotic strains in a biofloc system on the growth performance and disease resistance of red hybrid tilapia (Oreochromis spp.). Three different probiotics (Lysinibacillus fusiformis SPS11, Bacillus amyloliquefaciens L9, and Enterococcus hirae LAB3), commercial probiotics (MG1) and a mixed probiotics (MP) combining all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Biofloc systems may protect against bacterial infections, however, in this study fish fed with the commercial feed only in the biofloc did not show considerable protection against S. iniae , and when supplemented with probiotic treatments, the protection was increased. The same trend of probiotic effectiveness against tilapia pathogens following biofloc rearing has been reported in other recent studies (Mohammadi et al, 2021; Zabidi et al, 2021). One challenge for comparisons across trials is the actual microbial communities within the biofloc system and their inherent interactions with the tank system and the fish.…”
Section: Discussionsupporting
confidence: 86%
“…Biofloc systems may protect against bacterial infections, however, in this study fish fed with the commercial feed only in the biofloc did not show considerable protection against S. iniae , and when supplemented with probiotic treatments, the protection was increased. The same trend of probiotic effectiveness against tilapia pathogens following biofloc rearing has been reported in other recent studies (Mohammadi et al, 2021; Zabidi et al, 2021). One challenge for comparisons across trials is the actual microbial communities within the biofloc system and their inherent interactions with the tank system and the fish.…”
Section: Discussionsupporting
confidence: 86%
“…The most common lactic acid bacteria used in finfish culture include Carnobacterium, Enterococcus, Pediococcus, Lactobacillus, Lactococcus, and Leuconostoc genera (Merrifield and Ringo 2014). Zabidi et al (2021) reported that a probiotic mixture was able to prevent an increase in Streptococcus iniae and Streptococcus agalactiae. Individual bacterial species have specific limitations in nitrogen and phosphorus removal and pathogen control (Li et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Zabidi et al. (2021) reported that a probiotic mixture was able to prevent an increase in Streptococcus iniae and Streptococcus agalactiae . Individual bacterial species have specific limitations in nitrogen and phosphorus removal and pathogen control (Li et al.…”
Section: Introductionmentioning
confidence: 99%
“…To provide a viable alternative to prophylactic antibiotic administration, which is still done in some regions outside of the United States, an increasing amount of research has been conducted on the efficacy of probiotics (live microbes) and prebiotics (compounds metabolised by microbes) in promoting a healthy microbiome. For instance, these dietary supplements have the capability to support healthy fish physiology and microbiomes while also inhibiting pathogen proliferation (Al‐Hisnawi et al., 2019; Dawood et al., 2020; Giorgia et al., 2018; Hooshyar et al., 2020; Mora‐Sánchez et al., 2020; Park et al., 2017; Zabidi et al., 2021). Dietary changes especially affect the inhabitants of the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%